Oakeshott on the theory-practice problem: a reply to Terry Nardin. Issue 2 (3rd April 2015) - Smith,
Abstract : This is a reply to:Nardin, Terry. 2015. "Oakeshott on theory and practice." Global Discourse. 5 (2): 310–322. http://dx.doi.org/10.1080/23269995.2014.976921 .